Estudo teórico de complexos de hidrogênio heterocíclicos com enfoque na determinação dos mecanismos de reação - Silva, Jefferson José Soares da (2006)
In the present work the molecular properties of heterocyclic hydrogen complexes: oxirane (C2H4O), methyloxirane (H3C-C2H3O) and hydroxi-oxirane (HO-C2H3O), as well as the respective ring open reaction by fluoridric acid has been investigated by using quantum chemistry methods. In this way, molecular properties of hydrogen complexes, such as oxirane---HF (C2H4O---HF), methyloxirane---HF (H3C-C2H3O---HF) e hydroxi-oxirana---HF (HO-C2H3O---HF), has been investigated as well. The quantum chemistry methods used were: ab initio (HF) and DFT (B3LYP and PBE1PBE) with the base set 6-311++G(d,p). The optimized structures for the hydrogen complexes and the reaction products were used in order to obtain the structure of the transition state and reaction path. The results yield that the mechanism for ring open involving the reagent HO-C2H3O-HF was kinetically and thermodynamically more favorable. The nucleofilic attack to the more substituted carbon is the preferential one. The reactivity order of the ring opened mechanism was: HO-C2H3O-HF > H3C-C2H3O-HF > C2H4O-HF.